KOMUNIKASI NON-VERBAL PADA REMAJA BERKEBUTUHAN KHUSUS DALAM MENARIK PERHATIAN LAWAN JENIS - Chrisdina, Chrisdina (Fakultas Komunikasi, Sastra, dan Bahasa, 2018)
Autistic people might suffer from misconceptions in communication when they reach adolescent or as puberty affects their hormonal balance. To show their feelings to the opposite sex, autistics teenagers might communicate with each other by exchanging non-verbal symbols. Such condition occurred at the London School Beyond Academy (LSBA) Jakarta skills training institute. The present study aims to investigate non-verbal communications among young people with autism which take place when they are attracted to the opposite sex in LSBA. To investigate the matter, descriptive qualitative method was applied. Data is collected through interviews and observations. The results suggest non-verbal communication is not only understood by two teenagers who are attracted to each other, but also by their friends. The results show that non-verbal communications through symbols are common things among adolescents with special needs and such communication can be interpreted easily. The simplicity of perceived symbols and direct meaning from their friends make it easier for teenagers with special needs to express their feelings. Parents need to provide their supports by giving normative familial boundaries. In addition, educators can get involved by providing understanding of psychological stages of autistic teenagers. However, educators still need to give boundaries to those teenagers such as forbidding them from doing direct contact when no one is watching.  under